Sources of Employment Growth by Occupation and Industry in Canada - Betts, Julian; McCurdy, Thomas (Relations industrielles / Industrial Relations, 1993)
This paper uses Canadian input-output and census data from 1961, 1971 and 1981 to decompose employment changes during each decade into nine sources. The goals are to identify: the main sources of growth in aggregate employment; factors which facilitated the more rapid rate of growth of employment in the 1970s; and some reasons for intersectoral shifts of employment and changes in the occupational composition of employment. We pay particular attention to the changing importance ofthe 'information economy '.